>>667545>>667640Anyways, there is no easy way to solve that equatrion. My guess is, you probably made a typo and you meant x^2+x = 4

If that is the case, then you can easily solve that using the quadratic formula as such:

x^2 + x = 4

x^2 + x -4 = 4 - 4

x^2 + x - 4 = 0

Using the quadratic formula

[-b +/- sqrt(b^2-4ac)]/2a, where:

a=1

b= 1

c=-4

We have:

[-1 +/- sqrt(1^2-4*1*-4)](2*1)

[-1 +/- sqrt(1-(-16))]/(2)

[-1 +/- sqrt(1+16))]/(2)

[-1 +/- sqrt(17)]/(2)

x1 = (-1 - sqrt(17))/2 = -2.5616...

x2 = (-1 + sqrt(17))/2 = 1.5616...